Membaca â€œParadigmaâ€ Pendidikan dalam Bingkai Multikulturalisme - Aris Saefulloh (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: Indonesia have acquainted with multiculturalism from a long time ago, explicit from Kitab Sutasoma by Empu Tantular. From this book, Indonesia adopts jargon Bhineka Tunggal Ika to provide a place for diversity that very complex. However, this complex diversity if didnâ€™t managed carefully will trigger division through primordial conflict. This article will suggest importance of education that endorse multiculturalism as understanding to diversityâ€”that actually have one direction. This article is important if we look at recent times where do many ethnic conflicts like at Poso, Kupang, Sampit, Sambas, and several regions. If its let prolonged, those conflict can deprave solidarity spirit of Indonesian nation.Â